Optimal design of water networks involving single contaminant - Handani, Zainatul Bahiyah; Wan Alwi, Sharifah Rafidah; Hashim, Haslenda; Abdul Manan, Zainuddin (Penerbit UTM Press, 2009)
This work presents the development of a systematic technique to target freshwater consumption and wastewater generation to achieve the maximum water recovery for systems involving single contaminant. A generic linear programming (LP) model has been developed based on water network superstructure to simultaneously generate the maximum water recovery targets and design minimum water network, for both mass transfer-based and non-mass transfer-based problems (i.e., global water-using operations). The approach is illustrated by using an urban case study involving a mosque and an industrial case study involving an acrylonitrile process. The results show the potential maximum freshwater and wastewater reduction are 43.4% and 49.3% respectively for Sultan Ismail Mosque, and 70.6% and 37.7% for acrylonitrile process, which agree with the previous study performed using water cascade analysis technique